2011
DOI: 10.1002/app.33984
|View full text |Cite
|
Sign up to set email alerts
|

Melt processing of poly(L‐lactic acid) in the presence of organomodified anionic or cationic clays

Abstract: Poly(L-lactic acid) (PLA) films are in use for various types of food packaging; however, a wider range of applications would be possible if the barrier properties of these films could be improved. To make such improvements, combinations of PLA with two nanofillers, laurate-intercalated Mg-Al layered double hydroxide (LDH-C 12 ) and a cationic organomodified montmorillonite (MMT) clay (CloisiteV R 30B), were investigated. The dispersion of these fillers in PLA by melt processing was explored using two methods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 65 publications
(74 reference statements)
6
46
0
1
Order By: Relevance
“…For other hand, the lowest value of this parameter was found for the nanocomposite containing 2 wt% of Zn/Al sebacate. These observations can indicate that some fillers exhibited, at certain concentrations, higher nucleation tendencies, giving rise to more uniform crystal sizes [1] .…”
Section: Polymeric Nanocompositesmentioning
confidence: 89%
See 3 more Smart Citations
“…For other hand, the lowest value of this parameter was found for the nanocomposite containing 2 wt% of Zn/Al sebacate. These observations can indicate that some fillers exhibited, at certain concentrations, higher nucleation tendencies, giving rise to more uniform crystal sizes [1] .…”
Section: Polymeric Nanocompositesmentioning
confidence: 89%
“…This finding might be due to variations in the molecular weight of PLA since it is known that the PLA melting point is influenced by polymer chain length [12] . Some authors [1,10,12] reported the decrease in molecular weights of PLLA nanocomposites containing LDHs. This reduction in molecular weight could arise due to release of tightly bound water in the LDH interlayer spacing which would cause hydrolytic degradation of PLA chains.…”
Section: Polymeric Nanocompositesmentioning
confidence: 99%
See 2 more Smart Citations
“…The melting enthalpy of 100% crystalline PLA was taken as ΔH m°= 93 J/g. 25 After considering the effect of flame retardant loading (ϕ), crystallinity was calculated with eq 1: 26,27 Thermogravimetric analysis−infrared spectrometry (TG− IR) was conducted using the TGA Q500 IR thermogravimetric analyzer that was linked to the Nicolet 6700 FTIR spectrophotometer. About 5−10 mg of the sample was put in an alumina crucible and heated from 30 to 700°C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%